Liquid exfoliation of five-coordinate layered titanate K2Ti2O5 single crystals in water. Issue 28 (29th June 2022) - Hayashi, Fumitaka; Furui, Kenta; Tatewaki, Nanako; Sudare, Tomohito; Kashiwazaki, Maru; Shiiba, Hiromasa; Tanaka, Hideki; Koyama, Michihisa; Terashima, Chiaki; Teshima, Katsuya
Abstract : Millimeter-sized K2 Ti2 O5 single crystals were grown from a KCl–KOH mixed flux using a flux-evaporation assisted method. H2 O was found to be the best solvent for the liquid exfoliation of K2 Ti2 O5 crystals. Abstract : Liquid exfoliation is a scalable and effective technique for preparing two-dimensional materials but suffers from several issues, including low yields and lack of control over the lateral size of the nanosheets. Herein, we report the flux-evaporation-assisted growth of millimeter-sized K2 Ti2 O5 (KTO) single crystals and their liquid-phase hydrothermal exfoliation to form nanosheet colloids in water. The parent millimeter-long KTO single crystals were grown from a KCl–KOH flux at 900 °C in air flow, and several solvents for the exfoliation of KTO were investigated. As a result, H2 O was found to be the best solvent for exfoliation. Field-emission scanning electron microscopy analysis of a typical 2D KTO nanosheet revealed that its lateral size was 5–15 μm, consistent with dynamic light scattering results. Scanning probe microscopic analysis showed that there was some dispersion in the degree of exfoliation of the nanosheets and that approximately 60% of the nanosheets had thicknesses of less than 10 nm. In addition, X-ray absorption near edge structure (XANES) measurements of the KTO nanosheet colloid provide evidence that the KTO crystals undergo partial hydrolysis in water to generate hydroxyl groups on the surface, which weaken the interactions between the anionic frameworks and interlayer cations and accelerate exfoliation. Density functional theory calculations of the exfoliation energy reveal that this hydrolysis reaction decreased the exfoliation energy compared to that of bare KTO.